Impact of Self-Heating Effect on DC and AC Performance of FD-SOI CMOS Inverter - Kang Hee Lee; Mincheol Kim; Jongmin Lee; Jang Hyun Kim (IEEE Journal of the Electron Devices Society)
We analyzed the impact of self-heating effect (SHE) on fully depleted-silicon on insulator (FD-SOI) CMOS inverter at the 28 nm technology node, considering both DC and AC operations. Specifically, we focused on investigating the principles behind how SHE influences inverter operating characteristics. To analyze the operating characteristics, we employed 2-D technology computer-aided design (TCAD) mixed mode simulation by Synopsys SentaurusTM. In DC operation, the maximum lattice temperature for n-MOSFET and p-MOSFET are 436 K and 449 K, respectively, resulting in a current degradation of 7.9%. Due to the shifted p/n ratio, the gain also varied, with values of 3.65 V/V for without SHE and 4.21 V/V for with SHE. In AC operation, the maximum temperature varies for each operating frequency: 439 K, 358 K, 324 K, and 319 K, from 10 MHz to 4 GHz. Consequently, the rate of p/n ratio deviation and the rate of voltage change over time vary accordingly. SHE exhibits a faster rate of change, showing a difference of 5.43% at 10 MHz. Analysis of propagation delay through an inverter chain showed a 10% increase at 10 MHz. The results indicate that with SHE, the propagation delay increases, and the slew rate becomes steeper, suggesting improved switching characteristics and gain. However, this unintended consequence highlights the necessity of considering SHE-induced changes in CMOS inverter design to ensure reliable operation.